Diseño de estrategias aplicadas al medio ambiente apoyados por la Responsabilidad Social Empresarial en la empresa Textiles Lafayette (2021)
The concept of corporate social responsibility is becoming more important within organizations every day, but why is it so important? Because it is about the conservation of natural resources, resources that we know are non-renewable, that has led us to become aware and seek more environmentally friendly practices. But it will be that this work is only for companies or it belongs to everyone, we conclude that it belongs to everyone, since we share a planet that gives us everything to live but with actions that sometimes seem insignificant to us, such as throwing out a paper to the floor we are destroying it and let us remember that it is the only place we have to live, so why not act differently, why not make an effort and improve.